Comparing empowering, transformational, and transactional leadership on supervisory coaching and job performance: A multilevel perspective. - Lee MCC; Ding AYL (The Institute of Psychology, Chinese Academy of Sciences and John Wiley & Sons Australia Lt, 2020)
With a leader being able to possess different types of leadership styles, there is a lack of literature investigating which leadership style best facilitates supervisory coaching behavior. The current study aimed to investigate which leadership style would exhibit supervisory coaching behavior, and if supervisory coaching behavior would mediate the relationship between leadership styles and job performance. The study compared the effects of three leadership styles-transformational, transactional, and empowering leadership-on supervisory coaching behavior, which has been reported to influence job performance. A multilevel approach was adopted in this study using 500 employees from 65 organizations within Malaysia. The study found that only empowering and transactional leadership styles exhibited supervisory coaching behavior, which in turn mediated their relationships with job performance. Overall, the findings suggest the importance of leadership styles that prioritize employee development, as these would lead to improved job performance in employees.
Caul read and publish
Keywords: empowering leadership; job performance; supervisory coaching; transactional leadership; transformational leadership; Humans; Job Satisfaction; Leadership; Malaysia; Mentoring; Power, Psychological; Surveys and Questionnaires; 1701 Psychology; 1702 Cognitive Sciences